Coloniality and its Future - Anzi, Achia (Kronos: Southern African Histories, 2022)
Decoloniality emerged in the last two decades as a new mode of critique against colonialism and coloniality. While its insights are inspired by dependency and postcolonial theories, decoloniality challenges them both, particularly their inability to depart with modern Western epistemology. Written in response to Arjun Appadurai's recent critique of On Decoloniality by Catherine E. Walsh and Walter D. Mignolo, this article attempts to articulate decoloniality's approach to epistemology and discourse analysis. Whereas Appadurai describes Walsh and Mignolo's position as an anachronistic attempt to "return to the precolonial past," this article underlines his inability to transcend the modern linear order of time.